Metrication in mathematics for teachers' colleges in Guyana - Mohan-Ram, Vivekanand (1976)
In this mathematics curriculum, the metric system was suggested in place of the imperial system. The former was in keeping with the changes that were taking place in mathematics programmes in the early seventies. It suggested the five basic metric units as a core--the metre, the litre, the gram, the second, and the degree Celsius. These were expanded to include every possible aspect of the unit to aid interpretation, transfer, and understanding of the unit. Suggestions were made as to how the metric system should be introduced at the college and school levels, especially when the imperial system was the system used. The curriculum contained the major sections, namely, rationale, content, objectives, material to be used, teaching aids, content and evaluation. It also briefly suggested how it should be taught at the primary level. A list of specific teaching aids and appropriate metric text books are appended
Keywords: Mathematics